Mead production: selection and characterization assays of Saccharomyces cerevisiae strains - Pereira, Ana Paula (2011)
http://apps.isiknowledge.com/full_record.do?product=UA&search_mode=GeneralSearch&qid=10&SID=V12mKh9k9n8jHN@CK7o&page=1&doc=1&colname=WOS